Assessing the Prospects of Restorative Justice in Multicultural Societies Menakar Prospek Keadilan Restoratif di Masyarakat Multikultural - Dwi Ari Kurniawati (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2024)
This study aims to analyze the application of the concept of restorative justice in the criminal justice system in Indonesia based on local wisdom values. The urgency of this study is based on the need for a more humane and holistic solution in resolving criminal cases, considering that the dominant retributive approach is considered less effective and fair. This research method uses normative juridical with a conceptual approach and a comparative approach. The results of the study show that the application of restorative justice that takes local wisdom into account can reduce the workload of the court, increase victim participation, and encourage the responsibility of the perpetrator in repairing the damage caused. In conclusion, the concept of restorative justice that is integrated with local cultural values ??such as deliberation, consensus, and mutual cooperation has great potential to create a fairer and more effective justice system. The novelty of this study lies in the comprehensive approach that combines restorative justice with local wisdom, as well as recommendations for the development of policies and regulations that support its widespread implementation in Indonesia. Keywords: Local Wisdom; Restorative Justice; Criminal.